Characterization of vacuum plasma sprayed cobalt - nickel- chromium - aluminum - yttrium coatings - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper analyzes the influence of the plasma spray distance on the microstructure and the mechanical properties of the Co32Ni21Cr8Al0.5Y coatings deposited with the vacuum plasma spraying (VPS) procedure. The microstructure and the mechanical properties of the plasma spray coatings were determined by the interaction of the Ar/H2 plasma ions with the powder particles when the transfer of the speed and temperature of ions on the powder particles occurs. The effect of interaction directly depends on the time of the interaction between ions and powder particles, which is defined by the plasma spraying distance. The powder is deposited by the plasma gun F4 at three substrate distances: 270, 295 and 320 mm. The coating with the best structural and mechanical properties was tested on the oxidation in a furnace for heat treatment without protective atmosphere at 1100°C in a period of 240 hours. The morphology of the powder particles was examined on the SEM. The microstructure of the layers in the deposited condition was tested by light microscopy. The coating with the best mechanical properties was electrolytically etched with 10% oxalic acid solution H2C2O4x2H2O. The analysis of the microstructure of the etched coating was performed by light microscopy and on the SEM, before and after testing the coating on oxidation. The microstructural analysis of the deposited layers was performed in accordance with the ’Pratt-Whitney’ standard. The mechanical properties of the layers were assessed through the examination of microhardness by the HV0.3 method and through bond strength tensile testing.